2021
DOI: 10.3390/polym13234161
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose-Based Superabsorbent Polymer Gel Crosslinked with Magnesium Aluminum Silicate for Highly Removal of Zn (II) from Aqueous Solution

Abstract: Lignocellulose (LCE) was ultrasonically treated and intercalated into magnesium aluminum silicate (MOT) clay to prepare a nano-lignocellulose magnesium aluminum silicate polymer gel (nano-LCE-MOT) for the removal of Zn (II) from aqueous solution. The product was characterised using nitrogen adsorption/desorption isotherm measurements, Fourier-transform infrared spectroscopy, scanning electron microscopy and energy-dispersive X-ray spectroscopy. The conditions for the adsorption of Zn (II) on nano-LCE-MOT were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In a report on the removal of Zn(II) by nano-lignocellulose Mg–Al silicate polymer gels, adsorption mechanisms were investigated and adsorption kinetics and isothermal modelling analysis were performed to achieve the optimal adsorption of Zn(II) (An et al , 2021). The presence of hydroxyl and carboxyl groups at the activated sites on the surface of the polymer gel revealed that they formed new chemical bonds with Zn(II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a report on the removal of Zn(II) by nano-lignocellulose Mg–Al silicate polymer gels, adsorption mechanisms were investigated and adsorption kinetics and isothermal modelling analysis were performed to achieve the optimal adsorption of Zn(II) (An et al , 2021). The presence of hydroxyl and carboxyl groups at the activated sites on the surface of the polymer gel revealed that they formed new chemical bonds with Zn(II).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of hydroxyl and carboxyl groups at the activated sites on the surface of the polymer gel revealed that they formed new chemical bonds with Zn(II). The main adsorption process was chemisorption, although ion exchange and electrostatic attraction could also occur during the adsorption (An et al , 2021). Regarding the superior nitrate adsorption characteristics and the mechanism of the synthesized allophane, it is considered that the cation- and anion-exchange capacities of soil allophane depend on the pH of the solution, which is interpreted as the development of negative and positive charges resulting from the dissociation and uptake of H + through the edge OH groups bonded to Si and Al (Wada, 1967).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption kinetics followed a pseudo-second-order model, and the Langmuir isotherm model was applied. The gel demonstrated a maximum adsorption capacity of 513.48 mg/g, and optimal adsorption conditions and desorption methods were identified [ 55 ].…”
Section: Environmental and Pollution Controlmentioning
confidence: 99%
“…The efficiency of SAPs in removing pollutants varies depending on the type of contaminant, pointing to the necessity for optimization across a wide range of applications. The use of cellulose additives in cement composites and the environmental effects of materials like kaolin require specific approaches and additional research [ 54 , 55 ]. Finally, developing nanocellulose-based composites and other specialized SAPs often involves complex synthesis processes, high production costs, and safety concerns, particularly related to microbial interactions and the use of toxic crosslinkers.…”
Section: Limitations In Using Sustainable Superabsorbent Polymersmentioning
confidence: 99%